Red Blood Cell Membranes in Donors of Different Age Groups - V. V. Moroz; Ye. K. Kozlova; M. S. Bogushevich; A. M, Chernysh; U. A. Bliznyuk; A. P. Kozlov; P. Yu. Alekseyeva (Общая реаниматология, 2006)
The paper describes an electroporation technique in order to evaluate its action on a biological membrane in donors of different age groups. It is shown that the older the donor is, the higher the rate of hemolysis is. Thus, owing to its simplicity, the electroporation technique may be clinically tested to diagnose the status of red blood cell membranes in subjects from different age groups for further studies.